Studies in synthetic carbohydrate chemistry: Part 1. Nitromethane cyclization of sugar polyaldehydes with a view to the synthesis of nitrocyclodextrins. Part 2. Approaches to the synthesis of 2-(R)-fluoro-daunosamine, a carbohydrate moiety for an antitumor drug. - Shu, Youn Yuen. (University of Ottawa (Canada), 1992)
Part I. Polyaldehydes derived by periodate oxidation from methyl 4,6-O-benzylidene-alpha-D-glucopyranoside, phenyl 4',6'-O-benzylidene-alpha-maltoside, and 6-deoxy-beta-cyclodextrin incorporate nitromethine functionalities by base-catalyzed reaction with nitromethane according to the general principle of nitroalkane cyclization of sugar dialdehydes, leading to 3-deoxy-3-nitro heptoseptanosides, 3,3'-dideoxy-3,3'-dinitro-disaccharides, and "nitro 6-deoxy-beta-cyclodextrin", respectively. Chapter 1. Methyl 5,7-O-benzylidene-3-deoxy-3-nitro-alpha-D- glycero-D-ido-heptoseptanoside was debenzylidenated, and the resulting nitrotetrol was acetylated. A twofold reductive dehydroacetoxylation of the nitro tetraacetate at C-2 and C-4, and concomitant deacetylation at O-5 and O-7 then resulted in a crystalline mixture of methyl 2,3,4-trideoxy-3-nitro-alpha-D- ribo- and alpha-D-arabino-heptoseptanosides, further characterized as the corresponding 5,7-diacetates. Acetylation of methyl 5,7- O-benzylidene-3-deoxy-3-nitro-alpha-D-glycero-D- ido-heptoseptanoside with acetic anhydride and sodium acetate gave a methyl 2-O-acetyl-5,7-O-benzylidene-3,4-dideoxy-3-nitro-hept-3-enoseptanoside, reduction of which afforded a methyl 2,3,4-trideoxy-3-nitro heptoseptanoside. Chapter 2. Reductive cleavage of the benzylidene acetal ring of phenyl 4',6'-O-benzylidene-alpha-maltoside derivatives was attempted by several methods. One approach led to a low yield of 4'-benzyl ether of phenyl alpha-maltoside. Sodium metaperiodate oxidation of phenyl 4',6'-O-benzylidene-alpha-maltoside and its 6-deoxy derivative led to di- and tetra-aldehydes. Nitromethane condensation of the aldehydes resulted in mono- and dinitro-disaccharides, respectively. The structural analysis was done by the aid of mass spectrometry. Chapter 3. Heptakis(6-deoxy)cyclomaltoheptaose (6-deoxy-beta-CD) was obtained in high yield via 6-bromo-, 6-iodo-, and 6-phenyl-6-thio-beta-CD. Periodate oxidation of the product gave 6-deoxycyclodextrin polyaldehyde, which was confirmed by sodium borohydride reduction and acetylation to give a macrocyclic polyacetal. Nitromethane condensation of the polyaldehyde resulted in "nitro 6-deoxy-beta-CD". Part II. In an attempt to synthesize of 2(R )-fluorodaunosamine, a carbohydrate moiety for an antitumor antibiotic 2'-(R)-fluorodaunorubicin, a possible precursor compound, namely methyl 3,6-dideoxy-3-trifluoroacetamido-alpha-L-galactopyranoside was synthesized via periodate oxidation of L-rhamnopyranoside, nitromethane cyclization, reduction of the nitro group, and trifluoroacetylation of the resulting amino group. Selective trifluoromethanesulfonylation at 2-OH of the product gave its 2-triflate. Reaction of the latter with tetrabutylammonium fluoride, however, did not lead to displacement by fluoride but gave an epimine. Simultaneous protection of the 3-amino and 4-hydroxyl groups of methyl 3-amino-3,6-dideoxy-alpha-L-galactopyranoside with ethyl chloroformate gave the 3-N,4-O-carbonyl derivative which was subsequently triflated at 2-OH. Reaction of this triflate with tetrabutylammonium fluoride also failed to introduce fluorine, and resulted in a tricyclic 2,3-epimino-3-N,4-O-carbonyl compound.
Keywords: Chemistry, Organic.